Implementasi Asas Keadilan dalam Pembentukan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 tentang Cipta Kerja (Sebagaimana yang Telah Ditetapkan Menjadi Undang-Undang) - Demson Tiopan (Faculty of Law, Maranatha Christian University, 2023)
Prosperity can be achieved through the realization of order and organization within society. The principle of justice serves as one of the indicators that determine the attainment of the desired order and organization. In the concrete legal context, the process of forming legislation is required to reflect the presence of the justice principle inherent within it. A legal product is considered to fulfill the justice principle if it falls under the category of responsive law. Responsive law takes into account both functional and procedural aspects of its formation. This research uses a normative juridical research method with a statutory approach. The statutory approach is an approach used by basing it on the provisions of the applicable laws and regulations. This research aims to examine the implementation of the principle of justice in the substance and formation Government Regulation in Lieu of Law on Job Creation (Perppu Cipta Kerja). Perppu Cipta Kerja is perceived to not reflect the justice principle as it lacks the elements characteristic of responsive law. Consequently, the Perppu Cipta Kerja is categorized as a legal product that does not embody the value of justice, falling into the classification of conservative legal products. Therefore, it is imperative for the government to conduct a reevaluation of the formation process and functional aspects, particularly regarding the substantive content, to ensure it aligns with the justice principles mandated by the law. This alignment would facilitate the realization of order and organization within society, ultimately contributing to the welfare of the populace.